COMPARISON OF PERFORMANCES OF BIOLOGICAL NUTRIENT REMOVAL SYSTEMS FOR MUNICIPAL WASTEWATER TREATMENT - Demir, Selami (YILDIZ TECHNICAL UNIV, 2020)
Performance of wastewater treatment processes depends on many factors including wastewater characteristics, environmental conditions and operating parameters. Several treatment processes have their own advantages and disadvantages in terms of treatment performance. Performances of anaerobic/anoxic/oxic (A(2)O), five-stage Bardenpho (fsB), University of Cape Town (UCT), and modified UCT processes for biological nutrient removal from municipal wastewaters were evaluated at various C:N:P ratios in primary effluent by keeping all other parameters identical to each other in each process. The comparison was based on steady-state removal efficiencies for chemical oxygen demand (COD), total Kjeldahl Nitrogen (TKN), total nitrogen (TN), and total phosphorous (TP). Simulations were performed using an MS Excel Visual Basic for Applications (VBA) tool based on Activated Sludge Model No.3 extended with biological phosphorous removal processes. Simulation results indicated that, for low-to-mid influent TKN/COD ratios, fsB process shows the best performance in terms of TN and TP removal. On the other hand, modified UCT process can be the best selection at high influent TKN/COD ratios if only phosphorous removal is of concern. Five-stage Bardenpho process must be selected for both nitrogen and phosphorous removal no matter the influent C:N:P ratio is.
Keywords: Enhanced municipal wastewater treatment; biological nutrient removal; nitrogen removal; phosphorous removal; process configurations; activated sludge modeling; PHOSPHORUS REMOVAL; MODEL; NITROGEN; A(2)O; TEMPERATURE; Engineering